Simultaneous characterization of metabolic, cardiac, vascular and renal phenotypes of lean and obese SHHF rats. - Gina Youcef (Public Library of Science (PLoS), 2014)
Individuals with metabolic syndrome (MetS) are prone to develop heart failure (HF). However, the deleterious effects of MetS on the continuum of events leading to cardiac remodeling and subsequently to HF are not fully understood. This study characterized simultaneously MetS and cardiac, vascular and renal phenotypes in aging Spontaneously Hypertensive Heart Failure lean (SHHF(+/?) regrouping (+/+) and (+/cp) rats) and obese (SHHF(cp/cp), "cp" defective mutant allele of the leptin receptor gene) rats. We aimed to refine the milestones and their onset during the progression from MetS to HF in this experimental model. We found that SHHF(cp/cp )but not SHHF(+/?) rats developed dyslipidemia, as early as 1.5 months of age. This early alteration in the lipidic profile was detectable concomitantly to impaired renal function (polyuria, proteinuria but no glycosuria) and reduced carotid distensibility as compared to SHHF(+/?) rats. By 3 months of age SHHFcp/cp animals developed severe obesity associated with dislipidemia and hypertension defining the onset of MetS. From 6 months of age, SHHF(+/?) rats developed concentric left ventricular hypertrophy (LVH) while SHHF(cp/cp) rats developed eccentric LVH apparent from progressive dilation of the LV dimensions. By 14 months of age only SHHF(cp/cp) rats showed significantly higher central systolic blood pressure and a reduced ejection fraction resulting in systolic dysfunction as compared to SHHF(+/?). In summary, the metabolic and hemodynamic mechanisms participating in the faster decline of cardiac functions in SHHF(cp/cp) rats are established long before their physiological consequences are detectable. Our results suggest that the molecular mechanisms triggered within the first three months after birth of SHHF(cp/cp) rats should be targeted preferentially by therapeutic interventions in order to mitigate the later HF development.